Post-truth and the political: Constructions and distortions in representing political facts. (March 2019) - Temmerman, Martina; Moernaut, Renée; Coesemans, Roel; Mast, Jelle
Abstract: Post-truth has become a buzzword in recent years, as a shorthand for strategic constructions and distortions by all parties in political communication. According to Gibson (2018), the endless reflexivity of late modernity and a loss of faith in institutions interactively give rise to a 'post-truth double helix'. Facts are reduced to ideological claims to be discursively contested, giving rise to such notions as ' true facts ' and ' alternative facts '. The features of the online media environment further accelerate this dynamic. Journalism – as one of the traditionally authoritative institutions – plays a leading part in this spiral of dwindling trust. The perspectivist view on journalism increasingly has led audiences and journalists themselves to believe that there are no facts but only interpretations. Nevertheless, many journalists are still driven by the objectivity ideal which has traditionally sustained their authority as 'truth-speakers' (Tuchman, 1978). Others, however, call for transparency and multiperspectivalism (Gans, 2011) in order to limit inaccuracy and distortion as much as possible. This special issue of Discourse, Context & Media brings together a number of contributions exploring the discursive relation between political communication, news media and factuality. Mapping the eroding trust in true facts and the strategies of participants to deal with this 'post-truth era', this kind of research can provide valuable insights into evolutions which have a profound impact on every citizen, and democracy at large.